RELEVANSI INVESMENT OPPORTUNITY SET, KEBIJAKAN UTANG DAN UKURAN PERUSAHAAN DAN PENGARUHNYA TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA ( BEI ) PERIODE 2015 – 2017 - Darman, Darman (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This study aims to obtain empirical evidence about the effect of investment opportunity set, debt policy, and firm size on dividend policy. The population in the study are mining companies listed on the Indonesia Stock Exchange (IDX) in the period 2015-2017. Samples collected using purposive sampling method. A total of 14 (fourteen) companies were selected as samples. Types of associative research and testing tools using SPSS 20. Result of this research indicate that the independent variable of invesment opportunity set the, debt policy, and size measure of company masing-masingnya own the relation. Invesment Opportunity Set to dividend policy is positive strength with the correlation value 0,714. Policy Owe to dividend policy with the criterion is with the value 0,546 and Size measure of company with the weak relation with the value 0,303. While Invesment Opportunity Set to policy Owe with the value 0,454 with the relation is and also Relation of Invesment Opportunity Set The Invesment Opportunity Set to size measure of company with the value 0,717 with the Strong Relation. While Policy Relation Owe with the criterion is with the value 0,584. All the the relation own the small value signifikansi from 0,05 (significance). The influence on the independent variable investment opportunity set, debt policy, and company size simultaneously influence dividend policy. Meanwhile, the investment opportunity set and debt policy have a positive influence on dividend policy. While the size of the company has a negative influence on dividend policy. The results of the coefficient of determination show that 75,10% of the remaining 24,10% is explained by other variables not included in this study